Baseline Report: Africa Community Resilience Project (Tsaeda Amba Woreda, Eastern Tigray, Ethiopia) - Maxwell, Daniel; Tadesse, Girum; Mukwavi, Mary; Hailu, Shimelis; Zewold, Wolde Gebreal; Gebrekiros, Abraha (Tufts Archival Research Center, 2005)
Disaster Risk Reduction (DRR) programs encompass many different kinds of activities, but share the fundamental objective of enhancing the capacity of vulnerable communities to identify, reduce and manage risk, whether it be at the local, regional or national level. Ethiopia is one of the most food-insecure countries in the world, but only recently has the Food security problem begun to be understood in terms of a complete analysis of livelihoods, rather than simply a food supply problem.